ส่วนประสมการตลาดที่มีผลต่อผู้ตัดสินใจของหน่วยงานในมหาวิทยาลัยเชียงใหม่ในการซื้ออาหารว่างสำหรับการประชุม - พร้อมสิน ศีลอุดม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this research was to study marketing mix affecting decision makers of offices of Chiang Mai University towards purchasing snack for meetings. The data was collected using questionnaire distributed to 300 decision makers of offices of Chiang Mai University. The data was analyzed using descriptive statistics, namely frequency, percentage, mean, and F-test, to analyse the differences between marketing mix and average cost of snack and style of snack for meetings, at the reliability level of 95% (or at the statistical significance level of 0.05). The results of the research study showed that most questionnaire respondents (70.30 %) were female, 65.70% were 18-35 years old, 19.70% worked on general management, 28.30% worked in the fields of science and technology, 47.70% were university employees, 89.70% were operational employees, 32.00% (less than 40%) only occasionally made purchasing decision, 48.70% purchased for meetings in their departments 1 – 2 times per month, 42.30% of snack cost of was 20 – 29 Baht, 63.00% of the respondents favored western snacks, 41.70% favored hot coffee, 60.00% favored box-styled snack for meetings, 72.30% had been recommended by friends, and 87.70% focused on flavour. The questionnaire respondents ranked the overall marketing mix at the high level. All factors were ranked at the high level in the following order: place, price, product and promotion. The study of the sub-factors in each category showed that for product, the highest ranked sub-factor was the quality of the snack. For price, it was appropriateness of the price compared to the quality. For place, it was easy to contact. For marketing promotion, it was discount.